Examining customer-brand relationships: A critical approach to empirical models on brand attachment, love, and engagement - Mónica Gómez-Suárez (Administrative Sciences, 2019)
This study establishes the relationship among three concepts (attachment, love, and engagement) that have attracted the interest of both practitioners and researchers lately. Based on the consumer-brand relationship literature, a theoretical model is proposed. Using data obtained from a survey to 320 consumers from Madrid (Spain), the results show that only two constructs actually exist: attachment and active engagement, with love being part of attachment (passion) or engagement (long-term relationship). Thus, emotional attachment must be based on emotions that generate captivation. This admiration activates engagement, turning the consumer into the best brand promoter.
Keywords: 350; brand; consumer; customer; brand love; attachment; engagement; structural equation modeling (SEM)